Consumer Generated Advertising and Brand Trust in The Consumer Experience - Reeves, C (2010)
Increasing media clutter now exposes consumers to thousands of commercial messages every day (Gritten, 2007). The advent of the internet and technology over the past twenty years now means consumer-generated media such as blogs, podcasts, and online social networking sites are a further source (Gritten, 2007). Building brand trust remains, now more than ever, crucial to corporate marketers, in a world where consumers are losing faith in traditional marketing strategies. Social media has given the consumer a new voice, increasing interactivity in the consumer-brand relationship which provides new challenges and opportunities. This study examines the potential influence of consumer generated advertising on consumers’ trust in brands. In particular it focuses on symbolic brands. With academic literature asserting the death of mass media, this study evaluates one significant aspect of Web 2.0 as a new platform for corporate communication. It looks at the level of awareness of this new type of advertising, as well as the extent to which it yields an influence from the consumer perspective. The study begins with a detailed literature review of previous academic research and theory. Concepts, developments and theories have been explained with their relevance. From this emerged the research objective and aims. A number of in depth semi structured interviews were conducted with students and recent graduates to explore their attitudes and perspectives on the main issues. Interesting results and insights are presented, which represent the need for companies to gain a deeper understanding of the potential power of social media and consumer generated advertising and how it may be harnessed. Finally it is questioned whether the perceived threat of social media to corporate marketing control is as great as it is thought.